2009
DOI: 10.1073/pnas.0911915106
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive strategies of the influenza virus polymerase for replication in humans

Abstract: Transmission of influenza viruses into the human population requires surmounting barriers to cross-species infection. Changes in the influenza polymerase overcome one such barrier. Viruses isolated from birds generally contain polymerases with the aviansignature glutamic acid at amino acid 627 in the PB2 subunit. These polymerases display restricted activity in human cells. An adaptive change in this residue from glutamic acid to the human-signature lysine confers high levels of polymerase activity in human ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
383
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(405 citation statements)
references
References 44 publications
18
383
3
1
Order By: Relevance
“…Several amino acid changes in PB2 are important for the replication or virulence of influenza viruses in mammals (22)(23)(24)(25)(26)(27)(28)(29)(30). A detailed comparison of the amino acid differences among the EAH1N1 SIVs indicated that all of these viruses have mammalian-adapting mutations in their PB2 genes (SI Appendix, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Several amino acid changes in PB2 are important for the replication or virulence of influenza viruses in mammals (22)(23)(24)(25)(26)(27)(28)(29)(30). A detailed comparison of the amino acid differences among the EAH1N1 SIVs indicated that all of these viruses have mammalian-adapting mutations in their PB2 genes (SI Appendix, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations in the polymerase basic protein 2 (PB2) of the heterotrimeric viral polymerase and their structural consequences have been linked to host-species specificity and virulence factors in humans Mehle & Doudna, 2009;Subbarao et al, 1993). This link between PB2 point mutations and transmissibility has prompted further studies of proteins from different subtypes of influenza, including the nomination and approval of various PB2 constructs for study by the SSGCID.…”
Section: Parallel Purification Of Viral Proteins With the Protein Makermentioning
confidence: 99%
“…Intriguingly, fatal viral infections of humans with avian viruses of the H5N1 subtype that have retained the avian like PB2-E627 have been reported 9 . Moreover, the 2009 H1N1 pandemic virus also harbours PB2-E627, but additionally possesses a lysine at position 591 (PB2-E591K), which is able to partially, but not completely, compensate for the lack of the PB2-E627K mutation 10,11 , suggesting that other adaptive factors may account for the efficient replication of these viruses in humans. Other mutations in PB2, known to have a role in host adaptation, are the exchange of aspartic acid with asparagine at position 701 (PB2-D701N), which can confer high pathogenicity to avian H5N1 and H7N7 viruses in mice 4,12 and the substitution of threonine with alanine at position 271 (PB2-T271A), which has been suggested to enhance polymerase activity in mammalian cells 13 .…”
mentioning
confidence: 99%